2009
DOI: 10.1074/jbc.m109.029025
|View full text |Cite
|
Sign up to set email alerts
|

Repair of Laser-localized DNA Interstrand Cross-links in G1 Phase Mammalian Cells

Abstract: Interstrand cross-links (ICLs) are absolute blocks to transcription and replication and can provoke genomic instability and cell death. Studies in bacteria define a two-stage repair scheme, the first involving recognition and incision on either side of the cross-link on one strand (unhooking), followed by recombinational repair or lesion bypass synthesis. The resultant monoadduct is removed in a second stage by nucleotide excision repair. In mammalian cells, there are multiple, but poorly defined, pathways, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
100
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 87 publications
(104 citation statements)
references
References 87 publications
4
100
0
Order By: Relevance
“…Prior studies have shown that the NER damage recognition factor, XPC, which exists as part of a complex with HR23B, is an early arriver to DNA interstrand crosslink damage and directs a conventional repair response (16). To determine whether XPC facilitates the observed NEIL1 accumulation, we examined GFP-NEIL1 recruitment dynamics in cells deficient in XPC.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Prior studies have shown that the NER damage recognition factor, XPC, which exists as part of a complex with HR23B, is an early arriver to DNA interstrand crosslink damage and directs a conventional repair response (16). To determine whether XPC facilitates the observed NEIL1 accumulation, we examined GFP-NEIL1 recruitment dynamics in cells deficient in XPC.…”
Section: Resultsmentioning
confidence: 99%
“…In these experiments, photoactivated trioxsalen (psoralen) is used as the interstrand crosslinking agent, and angelicin is used as a control to generate monoadducts exclusively (Ref. 16; further details below). Our studies herein focus on the NEIL1 DNA glycosylase, since this protein has been previously shown to play multiple roles in interstrand crosslink repair (10,12).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations